The functional and anatomical organization of marsupial neocortex: Evidence for parallel evolution across mammals - Karlen, Sarah J. (2007)
Marsupials are a diverse group of mammals that occupy a large range of habitats and have evolved a wide array of unique adaptations. Although they are as diverse as placental mammals, our understanding of marsupial brain organization is more limited. Like placental mammals, marsupials have striking similarities in neocortical organization, such as a constellation of cortical fields including S1, S2, V1, V2, and A1, that are functionally, architectonically, and connectionally distinct. In this review, we describe the general lifestyle and morphological characteristics of all marsupials and the organization of somatosensory, motor, visual, and auditory cortex. For each sensory system, we compare the functional organization and the corticocortical and thalamocortical connections of the neocortex across species. Differences between placental and marsupial species are discussed and the theories on neocortical evolution that have been derived from studying marsupials, particularly the idea of a sensorimotor amalgam, are evaluated. Overall, marsupials inhabit a variety of niches and assume many different lifestyles. For example, marsupials occupy terrestrial, arboreal, burrowing, and aquatic environments; some animals are highly social while others are solitary; and different species are carnivorous, herbivorous, or omnivorous. For each of these adaptations, marsupials have evolved an array of morphological, behavioral, and cortical specializations that are strikingly similar to those observed in placental mammals occupying similar habitats, which indicate that there are constraints imposed on evolving nervous systems that result in recurrent solutions to similar environmental challenges.